Gentrified Foodways in North End Halifax - White, Megan (Cuizine)

(untitled) (McGill University Library, 2025)
The North End of Halifax has been subject to gentrification for decades. While much of the discourse about gentrification focuses on housing, this Petite Madeleine examines a less discussed type of gentrification, the gentrification of access to cultural foodways. The literature reviewed focuses on Black foodways, the forced displacement of Africville residents, and the how the foodscape of the North end has been influenced by white ways of eating. Told from the perspective of a North End resident who is a dietetic intern at the North End Community Health Centre, this paper highlights the inequalities in access to cultural foods stemming from racial marginalization, social exclusion, and how the preservation of foodways are used as resistance to systemic racism.